2018
DOI: 10.1111/ejn.14157
|View full text |Cite
|
Sign up to set email alerts
|

Illuminated night alters hippocampal gene expressions and induces depressive‐like responses in diurnal corvids

Abstract: Artificial light at night induces circadian disruptions and causes cognitive impairment and mood disorders; yet very little is known about the neural and molecular correlates of these effects in diurnal animals. We manipulated the night environment and examined cellular and molecular changes in hippocampus, the brain region involved in cognition and mood, of Indian house crows (Corvus splendens) exposed to 12 hr light (150 lux): 12 hr darkness (0 lux). Diurnal corvids are an ideal model species with cognitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 56 publications
3
41
0
Order By: Relevance
“…In the HC, which is involved in the processing of spatial information [ 19 , 20 ], the significant increase in the number of new neurons that were recruited under ALAN is contrary to the decrease that was found in Indian house crows [ 3 ]. However, these crows were acclimated, after being caught from the wild, only for a single week, shorter than the recommended three weeks to ensure thermogenic [ 36 ] and physiological [ 37 ] acclimation in birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the HC, which is involved in the processing of spatial information [ 19 , 20 ], the significant increase in the number of new neurons that were recruited under ALAN is contrary to the decrease that was found in Indian house crows [ 3 ]. However, these crows were acclimated, after being caught from the wild, only for a single week, shorter than the recommended three weeks to ensure thermogenic [ 36 ] and physiological [ 37 ] acclimation in birds.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a growing number of studies that demonstrate adverse effects of artificial light at night (ALAN) on the behaviour and physiology of many species (e.g., reviewed in [ 1 , 2 ]), still, in birds relatively little is known regarding its effects on brain plasticity. The few existing studies report a decrease in the numbers of newly formed neurons in the hippocampus (HC) of Indian house crows ( Corvus splendens ) [ 3 ], and a decrease in soma size of neurons in the HC and the lateral caudal nidopallium (NCL) in this species, suggesting reduced neuronal plasticity [ 4 ]. We have also studied the effect of ALAN on neuronal plasticity in another diurnal species, zebra finches ( Taeniopygia guttata ), which have excellent visual abilities [ 5 ] and their physiology, reproduction and survival are greatly affected by circadian and circannual rhythms [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence, largely accumulated from nocturnal rodents, suggests that artificial light at night (LAN) impacts a wide range of biological functions including sleep [1][2][3]. Similar LAN-induced negative effects have been found on daily cycles of the activity-rest and melatonin secretion, and on metabolism, reproduction, depression and cognitive performance in several songbirds including Indian weaver birds, Ploceus phillipinus [4]; blackbirds, Turdus merula [5]; great tits, Parus major [6][7][8]; Indian house crows, Corvus splendens [9]; zebra finches, Taeniopygia guttata [10,11] and tree sparrows, Passer montanus [12]. In particular, female great tits were awake for a greater portion of the night inside the nest-box when it was dimly illuminated [6].…”
Section: Introductionmentioning
confidence: 88%
“…Reaction to novel objects and novel food is known as one of the main factors determining the capacity of a species to thrive in an urban environment (41). The DCX gene is related to neuronal plasticity (56) and experimental approaches revealed that artificial light at night induces an overexpression of this gene linked to a change in behaviour and expression of depressive-like behaviour in crows (57). Finally, the CHRNA1 gene is associated with aggressive behaviour in chicken (58), and higher aggressiveness is commonly observed and hypothesized as adaptive in urban bird populations (59).…”
Section: Discussionmentioning
confidence: 99%